Lichens as air pollution assays on the Western Cape coast - Muofhe, Mmboneni Leonard (Department of Biological Sciences, 2017)
A pollution survey was done in Milnerton industrial area along three transects, the coastal road, the R27 road, and the N7 road. In this project lichens were used as pollution monitors and their availability, abundance and percentage cover were used to estimate the level of pollution. Lichen specimens were collected from St. James, which is far from the pollution source and put in the vicinity of the Caltex oil refinery for four month after which they were analysed for their fluorescence and chlorophyll content. In all transects, lichen species richness and percentage cover increased with distance from the oil refinery, suggesting that indeed lichens are sensitive to pollution and are therefore good air pollution bio-monitors. The fruticose growth forms especially Teloschistes and Usnea were shown in this study to be the most sensitive to pollution because none of them was recorded close to the oil refinery. Photosynthetic pigment analyses revealed that Parmelia and Xanthoria are affected differently by pollution. Parmelia showed chlorophyll a and b injury under high pollution conditions while Xanthoria showed high carotenoid injury. The results of this study indicate that the atmosphere in the Milnerton industrial area is heavily polluted, with the Caltex oil refinery being the main pollution source.